The significance of pre‐operative coronary interventions on outcome after pancreas transplantation. Issue 3 (25th January 2016) - Laurence, Jerome M.; Barbas, Andrew S.; Sapisochin, Gonzalo; Marquez, Max A.; Bazerbachi, Fateh; Selzner, Markus; Norgate, Andrea; McGilvray, Ian D.; Schiff, Jeffrey; Ross, Heather; Cattral, Mark S.
Abstract: Pancreas transplant candidates are at very high risk of coronary vascular disease. We hypothesized that the requirement for pre‐operative coronary intervention (PCI) may be associated with an adverse impact on short‐ and long‐term outcomes. Retrospective analysis of 366 consecutive primary pancreas transplants was undertaken. Outcomes were compared between recipients who had undergone PCI (n = 48) and those who had not (n = 318). In 48% (23/48) of instances, the PCI was initiated by the transplant cardiology evaluation. The recipients undergoing PCI were older than those not undergoing PCI (47.6 yr vs. 41.9 yr, respectively, p < 0.0001). Although not statistically significant, there was a higher rate of post‐operative major cardiovascular events (MCVE) in the PCI group (10.4%) compared with those not undergoing PCI (4.7%) (RR [95% CI]: 2.0 [0.90–4.5]; p = 0.17). In the long term, there were no differences in the rate of death with graft function (p = 0.77) or rejection (p = 0.17). There were no statistically significant differences between the groups with respect to patient (p = 0.54), kidney (p = 0.76), or pancreas (p = 0.63) graft survival. PCI is not a risk factor for short‐term perioperative events, and long‐term transplant outcomes are equivalent to patients not requiring PCI. PCI, by itself, should not be considered a contraindication for pancreas transplantation, but should raise awareness of perioperative risk.